Analisis kepadatan bakteri coliform di Sungai Siak (sekitar perumahan sari residence Kota Pekanbaru) - Arief Mubyarso; Yusni Ikhwan Siregar; Sofyan Husein Siregar (Jurnal Zona, 2017)
Faecal coliforms are indicative bacteria of fecal contamination. If the bacteria are found in the waters so that the waters has been polluted and can not be used as a source of drinking  water.  The  research  has  been  conducted  from April  to  June  2014  at  Sari Residence Housing which located in Siak riverbanks by using survey method. Densitydata of water coliform bacteria the preliminary test and assertion test in the laboratory according to SNI 2897-2008. Data analysis is using ANOVA statistics and compared with the water quality standards according to the Indonesian Government Regulation No. 82 year 2001 on the Management of Water Quality and Water Pollution ControlClass I and Class II. The results showed that the density of coliform bacteria in the Siak River (around Sari Residence Housing Pekanbaru city) ranged between 11267-15650jml/ 100mL and pass the drinking water quality standards and require special handlingfor the use of water. Siak River water (around Sari Residence Housing Pekanbaru city)not feasible for consumption according to PP 82 year 2001 class I and II on the drinkingwater requirements of 1000 jml/100mL and 5000 jml/100m